PEMAKNAAN DAN IMPLEMENTASI BAHASA LIDAH DARI PERSPEKTIF MAHASISWA TEOLOGI SEKOLAH TINGGI TEOLOGI BETHEL INDONESIA - Allen Jordi Ibrani; Gidion Hery Susanto (Phronesis: Jurnal Teologi dan Misi, 2023)
The term Tongues originates from the event of Pentecost. Even though there are differences in the context and concept of Tongues in Acts 2:1-13 and 1 Corinthians 12-14, it cannot be denied that both of them were events of the power of the Holy Spirit, which, in terminology, according to Luke and Paul used the word Tongues. The problem of speaking in tongues today often refers to 1 Corinthians 12-14, where this phenomenon is seen as something abnormal. This study aimed to measure the suitability between the understanding of Tongues and the implementation of Tongues. This is a descriptive qualitative research and text analysis with an exegesis approach. The research subjects in this study were 6 (six) Postgraduate students from Bethel Indonesia Theological College, where data collection was carried out using primary data by conducting in-depth interviews. At the same time, data analysis consists of data reduction, data display, and conclusion. Through research that has been done, it was found that the meaning of Tongues is a gift from God to carry out duties and functions for the body of Christ, the implementation of Tongues in worship is still carried out but is not an obligation, and Tongues is still relevant and valuable in congregational life.